Pengaruh Modal dan Pengalaman Unit Usaha terhadap Pendapatan Usaha Ekonomi Kreatif di Kota Ambon - Manuputty, Nathalya Vinisya; Pelamonia, Merryl; Rehatta, Geradin (Jurnal Pendidikan Ekonomi, 2024)
The growth of the creative economy sector in Ambon City has created new dynamics for small business management, requiring entrepreneurs to be more adaptive in facing challenges related to capital and business experience. This study aims to analyze the effect of capital and business experience on the income of creative economy business units in Ambon City. The research employs a quantitative method with a survey approach, collecting data from 67 business units and analyzing it using multiple linear regression. The results show that both capital and experience significantly influence business income, with capital having a more dominant contribution. These findings highlight the importance of effective capital management and sufficient business experience to drive income growth in creative economy businesses. This study enhances understanding of the key determinants of business income in urban creative sectors. The implications suggest the need to improve access to capital, provide business management training, and continuously develop business experience strategies so that entrepreneurs can remain competitive in the creative economy era.